2022
DOI: 10.1021/acs.inorgchem.2c02124
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Mixed States Caused by Spin-Elastic Interactions during First-Order Spin Phase Transition in Spin Crossover Compounds

Abstract: Recently, the possibility of exploiting the phenomenon of spin transition (ST) has been intensively investigated; therefore, it is particularly important to study the behavior of ST under various stimuli. Here, the shape and content of the intermediate phase of ST in Hoffmann-like compounds [Fe(Fpz) 2 M(CN) 4 ] (M = Pt, Pd) under external stimuli are studied. For this purpose, magnetic and Raman spectroscopy studies were carried out. In pressure-induced spin transition (PIST), a mixture of high-spin and low-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The value of P 1/2 Pt is less than that of P 1/2 Pd , a fact that is consistent with the order of ligand field strength reported in ref . The pressure interval difference between the ST of the two compounds, Δ P (Pd) > Δ P (Pt), is similar to the results described in ref , which may be related to the different mechanical properties of the compounds …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The value of P 1/2 Pt is less than that of P 1/2 Pd , a fact that is consistent with the order of ligand field strength reported in ref . The pressure interval difference between the ST of the two compounds, Δ P (Pd) > Δ P (Pt), is similar to the results described in ref , which may be related to the different mechanical properties of the compounds …”
Section: Resultsmentioning
confidence: 99%
“…Isoq-Pt shows a more sudden ST behavior than Isoq-Pd because the mechanical properties of Isoq-Pt change more significantly than Isoq-Pd before and after ST, which are conducive to the generation of spin domains. 52 In the variable-pressure Raman and IR spectra using KBr as a PTM, both Isoq-Pt and Isoq-Pd experienced "gradual" PIST under pressure, where the PIST behavior of Isoq-Pt changed particularly significantly, and the pressure interval of its ST was even larger than that of Isoq-Pd. Interestingly, in the X-ray diffraction experiment using microcrystalline powder, we found that both Isoq-Pt and Isoq-Pd showed the same PIST behavior as the single crystal.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…10 Importantly, both factors also influence the critical pressure where pressure-induced amorphisation occurs. 23 There has been interest in the pressure-dependent spin-state of MOF-related Hoffman-type clathrates [24][25][26] and the elastic properties of molecular Fe(II) SCO complexes, 27,28 highlighting that changing the spin-state significantly impacts B. The impact of the spin-state of metal centres within the metal-node on the mechanical properties of MOFs has not been explored to our knowledge.…”
Section: Introductionmentioning
confidence: 99%